Fuzzy rule-based system for evaluation of uncertainty transaction in cassava chain - Gabriel Filho, Luís Roberto Almeida [UNESP]; Pigatto, Giuliana Aparecida Santini [UNESP]; Lourenzani, Ana E. B. S. [UNESP] (Associação Brasileira de Engenharia Agrícola, 2015)
A fuzzy ruled-based system was developed in this study and resulted in an index indicating the level of uncertainty related to commercial transactions between cassava growers and their dealers. The fuzzy system was developed based on Transaction Cost Economics approach. The fuzzy system was developed from input variables regarding information sharing between grower and dealer on “Demand/purchase Forecasting”, “Production Forecasting” and “Production Innovation”. The output variable is the level of uncertainty regarding the transaction between seller and buyer agent, which may serve as a system for detecting inefficiencies. Evidences from 27 cassava growers registered in the Regional Development Offices of Tupa and Assis, São Paulo, Brazil, and 48 of their dealers supported the development of the system. The mathematical model indicated that 55% of the growers present a Very High level of uncertainty, 33% present Medium or High. The others present Low or Very Low level of uncertainty. From the model, simulations of external interferences can be implemented in order to improve the degree of uncertainty and, thus, lower transaction costs.

Este trabalho apresenta um sistema baseado em regras fuzzy que resultou em um índice que indica o nível de incerteza relacionada com as transações comerciais entre produtores de mandioca e de seus compradores, com base na abordagem da Economia dos Custos de Transação. O sistema fuzzy foi desenvolvido utilizando como variáveis ​​de entrada Previsão de Demanda/compra, Previsão de Produção e Compartilhamento de informações acerca de inovações de produção. A variável de saída consiste no nível de incerteza da transação entre vendedor e agente comprador, que pode servir como um sistema para a detecção de ineficiências. Entrevistas realizadas com 27 produtores de mandioca registrados nos Escritórios de Desenvolvimento Regionais de Tupã e Assis, São Paulo, Brasil, e 48 de seus compradores sustentaram o desenvolvimento do sistema. O modelo matemático aplicado na avaliação destes produtores indicou que 55% dos produtores têm relações comerciais com nível de incerteza Muito Alta, 25% Média ou Alta; e os demais, classificados entre Baixa ou Média. A partir dos resultados encontrados, simulações de ações poderiam ser implementadas para reduzir o grau de incerteza e os custos de transação envolvidos.
Sistema baseado em regras fuzzy para avaliação de incerteza na transação na cadeia de mandioca
Keywords: Fuzzy system; Transactions; Cassava; Uncertainty; Sistema Fuzzy; Transações; Mandioca; Incerteza